Validity and Practicality of Reaction Rate Student Worksheets based on Problem Based Learning Integrated with Ethnoscience to Train Critical Thinking Skills - Wahyuni, Puja Sri; Andromeda, Andromeda (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The objective research is to develop reaction rate student worksheets based on PBL integrated with ethnoscience and determine the validity and practicality. Type of research used is Educational Design Research with Plomp’s development models. There are two stage: preliminary research, prototyping and assessment, but this research is limited to the prototype III stage.  Subjects of this research consist of 3 chemistry lecturers FMIPA UNP, 2 chemistry teachers, and 9 students of Phase F SMAN 2 Padang. There are two instruments used, which are validity and practicality questionnaires.  Aiken's V formula was used to analyze the validity data obtained, while the practicality data was analyzed by the percentage method. The results showed an average V value of 0.87 in the valid category. Meanwhile, the practicality of the students' response was obtained at 89% and the teacher's response was 90% with a very practical category. Results of this research are the reaction rate student worksheets based on PBL integrated with ethnoscience for critical thinking is valid and practical, so this student worksheets can to continue to determine its effectiveness.Keywords: Liveworksheets, Problem Based Learning, Reaction Rates, Ethnoscience, and Critical Thinking.DOI: 10.23960/jppk.v13.i3.32269